Macrorchis Rondani 1877 - Sorokina, Vera S.; Pont, Adrian C. (Zenodo, 2010)
Genus Macrorchis Rondani, 1877 Macrorchis Rondani, 1877: 17 and 280. Type-species: Musca meditata Fallén, 1825, by original designation. Macrorchis meditata (Fallén, 1825) Musca meditata Fallén, 1825b: 87. Type-locality: no locality given (probably Sweden, Skåne province). Lectotype ♂, NHRS (designated by Pont, 1984b: 289). Siberian records: South Urals (Hennig, 1961a: 510); Urals and West Siberia (Zimin & El’berg, 1970: 560); south part of Tyumenskaya Oblast’, near Onokhino, subtaiga (Veselkin, 1966: 784, 788); Khanty-Mansiyskiy AO, Kondinskoye [as “Tyumenskaya Oblast’, Kondinskoye, 911 km from Tobolsk” in the original] (Lavčiev, 1971: 219); Respublika Sakha: Yakutsk, near mouth of River Aldan (Hennig, 1961a: 510); South Urals, West and East Siberia (Pont, 1986a: 198). General distribution: Palaearctic Region, from Europe east to China and Russia (East Siberia). : Published as part of Sorokina, Vera S. & Pont, Adrian C., 2010, An annotated catalogue of the Muscidae (Diptera) of Siberia 2597, pp. 1-87 in Zootaxa 2597 (1) on page 71, DOI: 10.11646/zootaxa.2597.1.1, http://zenodo.org/record/5318926 : {"references": ["Rondani, C. (1877) Dipterologiae Italicae prodromus. 6. Species italicae ordinis Dipterorum ordinatim dispositae, methodo analitica distinctae, et novis vel minus cognitis descriptis. Pars Quinta. Stirps XVII - Anthomyinae. Soc. Typograph., Parmae [= Parma], 304 pp.", "Fallen, C. F. (1825 b) Monographia Muscidum Sveciae. Part. IX & ultima. Berlingianis, Lundae [= Lund], pp. 81 - 94.", "Pont, A. C. (1984 b) A revision of the Fanniidae and Muscidae (Diptera) described by Fallen. Entomologica Scandinavica, 15, 277 - 297.", "Hennig, W. (1961 a) Muscidae. [Part, Lieferung 215.] In: Lindner, E. (Ed.), Die Fliegen der palaearktischen Region, 63 b, 481 - 528. Schweizerbart, Stuttgart.", "Zimin, L. S. & El'berg, K. Ya. (1970) Family Muscidae - true flies. In: Stackelberg, A. A. & Narchuk, E. P. (Eds), Keys to the insects of the European part of the USSR in five volumes (general editor G. Ya. Bey-Bienko). V (2). Diptera, Siphonaptera. Nauka, Leningrad [= St Petersburg], pp. 511 - 595. [In Russian.]", "Veselkin, G. A. (1966) Flies (Diptera), satellites of domestic animals and man, in the southern part of the Tyumen' Region. Entomologicheskoe Obozrenie, 45, 779 - 792. [In Russian.] [English translation in Entomological Review, Washington, 45 (4), 439 - 447.]", "Pont, A. C. (1986 a) Family Muscidae. In: Soos, A. & Papp, L. (Eds), Catalogue of Palaearctic Diptera. Volume 11. Scathophagidae - Hypodermatidae. Akademiai Kiado, Budapest, pp. 57 - 215."]}